A Monte-Carlo study of the fading of TL and OSL signals in the presence of deep-level competitors. (March 2020) - Chen, R.; Pagonis, V.
Abstract : In a previous paper, the issue of the evaluated lifetimes of thermoluminescence (TL) and optically stimulated luminescence (OSL) has been studied for the one-trap-one-recombination-center (OTOR) case, using the Monte-Carlo simulation. It was shown that under these circumstances, the decay curve of the electron occupancy along many thousands of years may not be exponential. Therefore, a lifetime determined from the results at short periods of time may not apply at longer periods of time. The decay at longer times was found to be slower than exponential and thus, one may observe longer lifetimes than predicted by the evaluated trapping parameters. In the present work we demonstrate that with a more complex model, namely, when an additional deeper trap is involved, the probability of getting an exponential decay of the signal is much larger. We study the fading of OSL and TL signals with different times elapsing between excitation and read-out under these circumstances, using a Monte-Carlo procedure, and show that with a significant deep-trap competitor, the extrapolation leading to the evaluation of the long-term stability of the signal is more viable. The results are compatible with previously existing evidence that the chances of having a TL peak with first-order characteristics are significantly larger in cases where a large deep trap, acting as a competitor, is present. Highlights: Stability of OSL and TL during very long periods of time. Fading of OSL and TL signal in a model with a competing trap. Monte-Carlo simulations. Exponential and non-exponential decay behavior.